New Cognition of Organ Hemodynamics: Artery-Perfusion-Vein - ZHAO Hua; WANG Xiaoting; LIU Dawei (Xiehe Yixue Zazhi, 2022)
The change of organ hemodynamics in critical patients is key to the impairment of organ function. Organ perfusion pressure is the direct power to ensure organ blood flow, which is affected by inlet organ pressure (arterial pressure) and outlet organ pressure (venous pressure). Different organs have unique perfusion pressure requirements and regulation systems for blood flow adjustment to match their physiological needs. As the supply side of organ perfusion, the blood flow of organs is influenced by mean arterial pressure (MAP)and autoregulation system. Organs with different autoregulatory abilities have different requirements for MAP, so the appropriate MAP should be decided according to the autoregulation range in clinical practice. However, organ blood flow perfusion is not only determined by the supply side, but also affected by venous reflux. Changes in arteriovenous gradient across important organs affect organ blood flow perfusion. Different organs have different tolerance levels for venous reflux disorders because their distance from the heart and the specificity of the organ itself. When conducting hemodynamic intervention, physicians should pay attention to the influence of different pressure changes on organ perfusion.